Proceedings of 7th International Conference on Physics and Astrophysics of Quark Gluon Plasma — PoS(ICPAQGP2015) 2017
DOI: 10.22323/1.242.0081
|View full text |Cite
|
Sign up to set email alerts
|

Indication of Collective flow and Transparency in p-p Collisions at LHC.

Abstract: . The mid-rapidity transverse momentum spectra of various hadrons and the available rapidity distributions of some strange hadrons produced in p-p collisions at LHC energy √s NN = 7.0 TeV have been studied using a Unified Statistical Thermal Freeze-out Model (USTFM). The calculated results are found to be in good agreement with the experimental data. The theoretical fits of the transverse momentum spectra using the model calculations provide the thermal freeze-out conditions in terms of the temperature and col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…By studying the spectra of hadrons, one can in principle comment on some of the properties of the strongly interacting hadronic matter. For example, by studying / ratio, it has been argued that transparency effects in case of high energy heavy-ion collisions may become operative [2]. Recently, it has been found that particle ratios of some of the hadrons, for example, + / + , − / − , and Λ/ − , show a sudden rise for a specified range of center of mass energy √ in case of heavyion collisions [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…By studying the spectra of hadrons, one can in principle comment on some of the properties of the strongly interacting hadronic matter. For example, by studying / ratio, it has been argued that transparency effects in case of high energy heavy-ion collisions may become operative [2]. Recently, it has been found that particle ratios of some of the hadrons, for example, + / + , − / − , and Λ/ − , show a sudden rise for a specified range of center of mass energy √ in case of heavyion collisions [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%